Franchise agreement strategy: contribution to R&D in Brazil and Poland / A estratégia o contrato de franquia: contribuição para P&D no Brasil e Polônia - Sichel, Débora Lacs; da Costa, Joyce Natividade (Revista Online de Pesquisa : Propriedade Intelectual, 2018)
The economic development is a consequence of the innovation procedure. This paper is about the innovation procedure in Brazil and in Poland. Both nations were re-democratized in the end of the 20th Century. The similarities of both countries do not reflect the development of IP (Innovation Procedure) since Brazil has got difficulties as a consequence of its economic crisis. This crisis didn’t allow the establishment of R&D centers. The paper also analyses the Polish integration in the European Union and how it has enabled the establishment of R&D centers through franchising.